2011
DOI: 10.1073/pnas.1110499108
|View full text |Cite
|
Sign up to set email alerts
|

Activation mechanism of theβ2-adrenergic receptor

Abstract: A third of marketed drugs act by binding to a G-protein-coupled receptor (GPCR) and either triggering or preventing receptor activation. Although recent crystal structures have provided snapshots of both active and inactive functional states of GPCRs, these structures do not reveal the mechanism by which GPCRs transition between these states. Here we propose an activation mechanism for the β 2 -adrenergic receptor, a prototypical GPCR, based on atomic-level simulations in which an agonist-bound receptor transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
441
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(497 citation statements)
references
References 39 publications
52
441
3
1
Order By: Relevance
“…Noticeably, the VG of BIA/b 2 AR is comparable with VG of BIA/b 2 AR/G a , although no G a is present at cytoplasmic region in BIA/b 2 AR. This is in agreement with the previous finding 24 that b 2 AR requires tens of microseconds to reset back to inactive states from a fully activated structure. However, we still observed that VG of BIA/b 2 AR already shrunk to B700 Å 3 compared with fully activated BIA/b 2 AR/ G a ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…Noticeably, the VG of BIA/b 2 AR is comparable with VG of BIA/b 2 AR/G a , although no G a is present at cytoplasmic region in BIA/b 2 AR. This is in agreement with the previous finding 24 that b 2 AR requires tens of microseconds to reset back to inactive states from a fully activated structure. However, we still observed that VG of BIA/b 2 AR already shrunk to B700 Å 3 compared with fully activated BIA/b 2 AR/ G a ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…Plausibly, ICL3-9 may have the ability to modulate movement of TM5 and promote a unique active conformation utilizing the helical extension of TM5 to unconventionally activate G s . It should also be noted that molecular dynamics simulations of the ␤ 2 AR show a weak relationship between conformational changes in the ligand-binding pocket and TM5/6 movement (8,53). Thus, the ability of the pepducin to promote conformational changes in this region does not depend on operation through an orthosteric mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…Using these approaches, it has been shown that there is a spectrum of conformations more complex than the simple active and inactive conformations. Specifically, computational approaches have provided evidence for metastable states that will be very difficult if not impossible to capture experimentally (32). Atomic-level simulations based on the available crystal structures of the ␤ 2 -adrenergic receptor reveal that different sections of the receptor (the ligand binding site, G protein binding site, and connector region) exhibit weak allosteric coupling and can occupy different conformations independently (32).…”
Section: Key Features Of Gpcr Structures Relevant To Drug Discoverymentioning
confidence: 99%
“…Specifically, computational approaches have provided evidence for metastable states that will be very difficult if not impossible to capture experimentally (32). Atomic-level simulations based on the available crystal structures of the ␤ 2 -adrenergic receptor reveal that different sections of the receptor (the ligand binding site, G protein binding site, and connector region) exhibit weak allosteric coupling and can occupy different conformations independently (32). The consequence of this loose structural relationship is that ligand efficacy only needs modulation of the equilibrium between different conformations to achieve distinct pharmacological outcomes.…”
Section: Key Features Of Gpcr Structures Relevant To Drug Discoverymentioning
confidence: 99%